Postpartum depression as the main predictor of impaired mother- infant bonding: A prospective study in a low-risk obstetric and neonatal cohort - Marielle Ribeiro Feitosa; Saint Clair Gomes Júnior; Emanuella Carneiro Melo; Antonio Brazil Viana Júnior; Paulo César de Almeida; Fernanda Rebelo (PLoS ONE, 2026)
Introduction The postpartum period imposes complex demands on women, making it essential to examine the mother-infant bond and its predictors to promote maternal and child health and inform public policy. Objectives To identify the primary predictors of the mother-infant bond within the first six months postpartum, considering sociodemographic, obstetric, and neonatal factors, as well as symptoms of postpartum depression (PPD). Methods A prospective cohort study was conducted with postpartum women in a northeastern Brazilian capital city, assessed at three and six months postpartum. The affective bond was measured using the Postpartum Bonding Questionnaire (PBQ), and PPD symptoms were evaluated with the Edinburgh Postnatal Depression Scale (EPDS). Associations were analyzed using multiple linear regression models and reported as β coefficients (95% confidence intervals). Results PPD was the strongest predictor of impaired mother-infant bonding. At the third month postpartum, PPD was significantly associated with total PBQ scores (β = 1.15, 95% CI: 0.93–1.37), impaired bonding (ABF1: β = 0.59, 95% CI: 0.46–0.72), and anxiety about the infant (ABF3: β = 0.28, 95% CI: 0.23–0.33). These associations remained significant at the sixth month postpartum across the same measures: total PBQ (β = 0.84, 95% CI: 0.61–1.08), ABF1 (β = 0.40, 95% CI: 0.26–0.54), and ABF3 (β = 0.24, 95% CI: 0.19–0.30). In contrast, social support emerged as a protective factor, negatively correlating with total PBQ scores (β = −8.53, 95% CI: −13.03 to −4.04) and impaired bonding (ABF1: β = −3.59, 95% CI: −6.26 to −0.93). Conclusion These findings identify PPD as a primary risk factor and social support as a crucial protective factor for mother-infant bonding. The results underscore the importance of routine PPD screening and the development of targeted interventions to enhance social support networks for women during the postpartum period.